Two-tier coordinated optimal scheduling of wind/PV/hydropower and storage systems based on generative adversarial network scene generation - Cai, Changchun; Li, Yuanjia; He, Yaoyao; Guo, Lei (Frontiers in Energy Research, 2023)
In order to achieve the economic consumption of renewable energy in a multi-energy power system including wind/PV/hydropower and energy storage, a two-tier coordinated optimal scheduling method based on generative adversarial network scenario generation is proposed in this paper. Firstly, an upper-tier optimization model for the operation of load and storage system is established and the objective is to minimize the load fluctuation and the cost of energy storage plants. Furthermore, a lower-tier optimization model to minimize the system operation cost and tide risk is established for the optimization operation of renewable energy generations. Secondly, improved generative adversarial network is proposed to generate the operation scenes to present the uncertainty characteristics of the wind and PV generations. Then, an improved coatis optimization algorithm is used to solve the proposed optimization problem. Finally, the IEEE30 bus system is chosen as the example system for verifying the proposed method, the simulation results show that the proposed method is validity and feasibility.